Primeiro registro de Paratanaisia bragai (Digenea: Eucotylidae) em arara Canindé (Ara ararauna) - Silva, Tarcísio Macedo [UNESP]; Pavan, Leonardo Fabrício [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfum [UNESP]; Milbradt, Elisane Lenita [UNESP]; Andreatti Filho, Raphael Lúcio [UNESP]; da Silva, Reinaldo José da [UNESP]; Okamoto, Adriano Sakai [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to provide the first report on a new host for the digenean Paratanaisia bragai in the caninde macaw Ara ararauna along with the pathological aspects of the infection in the new host. The microscopic findings revealed the presence of granulomatous interstitial nephritis. This study contributes towards knowledge of parasitism by P. bragai in A. ararauna, and emphasizes the need to use best practices in wildlife conservation parks.
First record of paratanaisia Bragai (Digenea: Eucotylidae) in blue and gold macaw (Ara ararauna)
Keywords: Birds; Histopathology; Macaw; Parasite; Wildlife